Implementation of the Village Tourism Area Development Program to Improve Local Original Income in Bone Bolango Regency - Mustafa, Iin; Tahir, Arifin; Rachman, Ayu Anastasya (Jurnal Mantik, 2025)
This study aims to analyze the implementation of a tourism village development program in relation to increasing Regional Original Income (PAD) in Bone Bolango Regency. The research focuses on three main aspects: tourism destination management, tourism human resource development, and the contribution of tourism villages to PAD. Furthermore, this study examines supporting and inhibiting factors in program implementation, including local government policy support, community involvement, limited human resources, and infrastructure availability. The research uses a qualitative approach with a descriptive design, where data is obtained through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the tourism village development program in Bone Bolango Regency still faces several obstacles, including limited human resource capacity, uneven supporting infrastructure, and disparities in development between tourism villages. However, support from local government policies, community involvement through the Tourism Awareness Group (Pokdarwis) and Village-Owned Enterprises (BUMDes), and the unique natural and cultural tourism potential are significant driving factors.